COGNITIVE IMPAIRMENT IN CHRONIC RENAL FAILURE PATIENTS UNDERGOING HEMODIALYSIS - Risdananda Desy Pramudyta; Mugi Hartoyo; Sri Utami Dwiningsih; Budiyati Budiyati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Background: Hemodialysis is a therapy to control uremia, fluid overload, and electrolyte imbalance in patients with chronic renal failure. However, the long time undergoing hemodialysis can risk causing cognitive function instability. The purpose of this study was to determine the presence of cognitive impairment chronic renal failure patients undergoing hemodialialysis. Methods: Type of quantitative research using cross-sectional correlational analysis research design, conducted on 121 samples with purposive sampling technique. Data collection was done using the Montreal Cognitive Assessment questionnaire using the Pearson Product Moment test. Results: The results showed that the majority of respondents were 46–65 years old, male; their last level of education was college; and the majority did not work. The long time undergoing hemodialysis is 120 months, with an average of 46 months. Most respondents experienced mild cognitive function impairment with memory domain, followed by visuospatial and attentional cognitive domains that cause the risk of dementia. Conclusion: There is a significant relationship between the long time undergoing hemodialysis and the cognitive function of chronic renal failure patients at RSUP Dr Kariadi Semarang (p = 0.000), with a strong relationship in the opposite direction (r = -0.610). The need to improve cognitive memory domain, such as conducting periodic cognitive screening with high-sensitivity instruments on hemodialysis patients who have a risk of severe dementia.